#### Question

Solve the following quadratic equations by factorization:

a^{2}x^{2} - 3abx + 2b^{2} = 0

#### Solution

a^{2}x^{2} - 3abx + 2b^{2} = 0

⇒ a^{2}x^{2} - 2abx - abx + 2b^{2} = 0

⇒ ax(ax - 2b) - b(ax - 2b) = 0

⇒ (ax - b)(ax - 2b) = 0

Therefore,

ax - b = 0

ax = b

x = b/a

or,

ax - 2b = 0

ax = 2b

x = 2b/a

Hence, x = b/a or x = 2b/a

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: A2x2 - 3abx + 2b2 = 0 Concept: Solutions of Quadratic Equations by Factorization.